Maurice Blanchot : the refusal of philosophy - Bruns, Gerald L. (Johns Hopkins University Press, 1997)
As a novelist, essayist, critic, and theorist, Maurice Blanchot has earned tributes from authors as diverse as Jacques Derrida, Giles Deleuze, and Emmanuel Levinas. But their praise has told us little about what Blanchot's work actually says and why it has been so influential. In the first comprehensive study of this important French writer to appear in English, Gerald Bruns ties Blanchot's writings to each other and to the works of his contemporaries, including the poet Paul Celan. In a series of close readings, Bruns addresses the philosophical and political questions that have surrounded Blanchot and his writings for decades. He describes what is creative in Blanchot's readings of Heidegger's controversial works and examines Blanchot's conception of poetry as an inquiry into the limits of philosophy, rationality, and power.